HIPC relief: Too late, too little? Perspectives from a new qualifier, Tanzania - A. V. Y. Mbelle (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In 1970 the external debt of Tanzania, a least developed country, was 16.8 per cent of GDP and 58.6 per cent of exports. The ratio of per capita debt to per capita income was 14.4 per cent. By 2001 the debt had reached just over 100 per cent of GDP and over 11 times the value of exports, with a per capita debt to per capita income ratio of 102 per cent. By any wisdom this is a terrifying story. Efforts to address the debt burden have involved own initiatives and global initiatives, the latest being the enhanced HIPC Initiative. What are the new prospects? This paper attempts to assess the potency of the HIPC Initiative in addressing the key agenda items in Tanzania: poverty reduction/eradication and resolving the external debt burden. The assessment involves analysing long-term trends in debt build-up and debt servicing obligations as well as Tanzania's efforts in order to become eligible for the enhanced initiative, though still attempting to achieve the completion point at over 16 months after reaching the decision point. The main conclusions are that relief comes too late to address adverse impacts and is too little to meet poverty targets. This calls on Tanzania to concentrate on complementary measures and the HIPC Initiative to undergo refinements like addressing the time lag between decision and completion points, and incorporating ratio of recurrent expenditure as a threshold level. – HIPC ; debt ; Tanzania
Keywords: F34; H6; O55; 330; Schuldenerlass; Tansania; HIPC